Risk of flooding of sewer pipelines caused by deposits in sewer - Kuliczkowska, Emilia (Instal, 2023)
A method of determining the risk of flooding of sewer pipelines caused by the occurrence of deposits in sewers has been proposed. The causes of flooding of sewage pipes were listed. The results of CCTV studies carried out by the Kielce University of Technology on the occurrence of sewer deposits in concrete, vitrified clay and PVC pipes, together with a proposal for their quantitative assessment, are given. Probability categories of flooding of sewer pipelines, categories of failure consequences and the risk of flooding of sewer are determined.